The IOU Consensus Recommendations for Empirical Therapy of Cystitis in Nursing Home Residents - Hanlon, Joseph T. (J Am Geriatr Soc, 2018)
OBJECTIVES: To establish consensus guidelines for empiric treatment of uncomplicated cystitis with anti-infectives in non-catheterized older nursing home residents. DESIGN: Two-round modified Delphi Survey. PARTICIPANTS: Expert panel of 19 clinical pharmacists. MEASUREMENTS: Comprehensive literature search, and development/review/edit of draft survey by the investigative group (i.e., 1 geriatric clinical pharmacist, 2 physicians from geriatric and 1 from infectious disease internal medicine). The expert panel rated their agreement with each of 31 recommendations for drugs of choice, dosing medications at various levels of renal function, drug-drug interactions to avoid, and duration of therapy by gender on a 5-point Likert scale (1= strongly disagree to 5=strongly agree). Consensus agreement was defined as a lower 95% confidence limit of ≥4.0 for the recommendation–specific mean score. RESULTS: The response rate was 95% for the first round and 3 recommendations achieved consensus (i.e., dosing for nitrofurantoin and trimethoprim/sulfamethoxazole in those without chronic kidney disease, and drug-drug interaction between trimethoprim/sulfamethoxazole and warfarin). In the second round, 90% responded and reached consensus on an additional 8 recommendations (2 for nitrofurantoin or trimethoprim/sulfamethoxazole as initial drugs of choice, 3 for dosing ciprofloxacin, nitrofurantoin, and trimethoprim/sulfamethoxazole at various levels of chronic kidney disease, and 3 drug-drug interactions to avoid: trimethoprim/sulfamethoxazole with phenytoin and ciprofloxacin with theophylline, or tizanidine) CONCLUSION: An expert panel of clinical pharmacists was largely able to reach consensus agreement on a number of recommendations for the optimal empiric treatment of cystitis with oral anti-infective medications in older nursing home residents. The recommendations were incorporated into a treatment algorithm for uncomplicated cystitis in non-catheterized nursing home residents and used in educational materials for health professionals in an ongoing controlled intervention study.